Batik Pemalang Organic Wastewater Composition and Simple Electrocoagulation-Filtration Treatment. Issue 1 (March 2020) - Pratiwi, N I; Sari, S R; Arifan, F; Wulandari, A T; Alkian, I; Mustasjar, B; Aji, M B F B
Abstract: Wastewater produced by batik industry in Cibelok Village, Pemalang that is disposed straight into the sewage will increase the concentration of Biochemical Oxygen Demand (BOD), ammonia (NH3 ), Chemical Oxygen Demand (COD), chromium (Cr), lead (Pb), watercolour, acidity (pH), and dissolved oxygen (DO). Disposed batik wastewater without treatment will contaminate the environment, mainly its water and soil. The main purpose of this research is to reduce the concentration of Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), ammonia (NH3 ), chromium (Cr), lead (Pb), watercolour, acidity, and dissolved oxygen (DO) by treating batik Cibelok's waste and not contaminate the surrounding environment. Laboratory test results on batik waste in COD, BOD, DO, ammonia, chromium, lead, colour, and acidity (pH). These results are not in accordance with the 2014 Waste Water Quality Standard Number 5 by the Regulation of the Minister of Environment of the Republic of Indonesia. Alternatives that have been done to treat Cibelok Village's batik waste is to lower dangerous substances concentration through electrocoagulation and filtration. The processes could lower COD level around 57.6%, ammonia 98%, chromium 85%, and BOD 67%. Reducing the concentration of the substance makes the batik waste safer and environmentally friendly when it's finally disposed to the sewage.